Validation of the short form of the remote work stress scale - Keser, Askin; Ertemsir, Esin; Basol, Oguz (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThis study aims to develop and validate a reliable and psychometrically robust Short Form of the Remote Work Stress Scale (SRWSS), derived from the original 15-item RWSS.Design/methodology/approachFollowing the three-phase, nine-step scale development framework by Boateng et al. (2018), the study involved qualitative item generation, expert reviews, pilot study, exploratory and confirmatory factor analyses, and validation with a sample of 602 remote workers from T & uuml;rkiye. The short form was tested for reliability, validity and path analysis performed via SmartPLS with the original form and its sub-dimensions.FindingsThe SRWSS demonstrated excellent internal consistency (a = 0.88), strong construct and criterion validity, and a high correlation with the original scale (0.94). Results showed that female, highly educated and non-managerial employees reported higher levels of stress. Age was negatively correlated with stress levels.Research limitations/implicationsThe sample is confined to a specific demographic (Turkish remote workers), necessitating cross-cultural validation to ensure generalizability.Practical implicationsThe scale enables quick stress assessments to inform targeted interventions and HR strategies in remote and hybrid work settings.Social implicationsFindings highlight demographic disparities in remote work stress, informing equitable workplace policy development.Originality/valueThis study pioneers the development of a validated, unidimensional 5-item scale, offering a novel, efficient instrument for assessing remote work stress, enhancing research and practice in HRM.
Keywords: Remote work; Work stress; Stress scale; Human resources management; Scale development; PLS-SEM; JOB STRESS; TECHNOLOGY; RELIABILITY; Computer Science